Effect of dual herb combinations on the growth performance, benefit cost ratio, blood profile, meat sensory qualities of broiler chickens - SINGH, JASWINDER; SETHI, A P S; SINGH, PARMINDER; SIKKA, S S (The Indian Journal of Animal Sciences, 2021)
Herbs being natural and within farmers acquaintance, are one of the most tried antibiotic alternative supplement to enhance the growth of poultry birds. Based on results of our previous studies on single herb supplementation, the present study was conducted to evaluate the effect of two herb combinations on growth performance of broiler chicks. One day old IBL-80 broiler chicks (Average weight ~37 g) were randomly distributed to five treatments with three replicates of each. Dietary regimen consist of control (CO), antibiotic group receiving 0.1 g/kg of oxytetracycline (AN), control diet with 0.5% cinnamon powder + 0.5% black pepper powder (CB), with 0.5% cinnamon powder + 1% whole leaf aloe vera powder (CA) and with 1% whole leaf aloe vera powder + 0.5% black pepper powder (AB). Weekly body weight gain and feed consumed were recorded and accordingly feed conversion ratio and benefit cost ratio were calculated. At the end of 5th week, 2 birds per replicate were sacrificed to determine the carcass characteristics, meat sensory evaluation, blood parameters, duodenum morphology and faecal microbial load. Data revealed that these herbal combinations have significant effect on the growth performance, FCR, nitrogen and calcium retention, blood parameters and overall acceptability of meat. Herbal combinations supplementations were significantly more profitable when used in starter phase only. Study concluded that these herbal combinations can be safely used in poultry ration to improve growth and customer oriented parameters in broiler chicken meat.